Workload Monitoring of Throwing Sport Athletes - Janel Havinga; Andrew Green; Clinton Swanepoel (Journal of Coaching and Sports Science)
Background: Throwing events involve the full use of the kinetic chain. Therefore, monitoring training loads is crucial to optimizing athlete adaptation while minimizing the risk of fatigue and long-term injury.